Lentiviral-Transduced Ectopic Expression of Androgenic Hormone in a Crustacean Hematopoietic Primary Cell Culture - Rotem-Dai, Noa; Weil, Simy; Greenshpan, Yariv; Abehsera, Shai; Manor, Rivka; Ofir, Rivka; Gazit, Roi; Rosental, Benyamin; Aflalo, Eliahu D.; Sagi, Amir (Frontiers in Marine Science, 2021)
Novel monosex biotechnologies in crustacean aquaculture involve the induction of sex reversal through manipulations of the androgenic gland (AG), and its most prominent factor, the insulin-like androgenic gland (IAG) hormone, during early developmental stages. In the giant freshwater prawn Macrobrachium rosenbergii, all-female populations are desirable for aquaculture, since the females can be stocked at higher densities and exhibit more uniform growth than males. Recently, a novel biotechnology for all-female aquaculture was developed based on injection into post larvae of suspended primary AG cells from mature M. rosenbergii males. However, this biotechnology depends on the availability of appropriate male donors and it requires delicate surgical procedures on the small endocrine AG to produce appropriate quantities of cells for the sex manipulation. We therefore established a new platform for the production of M. rosenbergii IAG (Mr-IAG) in hematopoietic cells. The method rests on the induction of ectopic Mr-IAG expression under the white spot syndrome virus (WSSV) immediate-early 1 (IE1) promoter via a novel lentiviral vector. Our results demonstrate that M. rosenbergii primary cells infected with the Mr-IAG lentiviruses are capable of transcription, translation and secretion of Mr-IAG in culture. Our new platform, which produces easy-to-harvest cells in abundance, could replace the AG cells used in the first step of the above-mentioned biotechnology for all-female aquaculture and, importantly, pave the way for producing monosex populations in other edible crustacean aquaculture species. In addition, a lentiviral system for crustacean cells provides a useful tool for basic and applied research in crustacean species.